Bringing out the treasure : inner biblical allusion in Zechariah 9-14 - Boda, Mark J.; Floyd, Michael H. (Journal for the study of the Old Testament. Supplement series ;, 2003)
It is generally agreed within Hebrew Bible scholarship that Zechariah 9-14 is filled with allusions to other books within the Hebrew canon. Rex Mason's doctoral dissertation in the early 1970s contributed significantly to the foundation of this consensus. However, although Mason's thesis remains a seminal work for those studying Deutero-Zechariah, it has never been published. This volume contains the first publication of that work together with reflections from leading biblical scholars who have published onZechariah 9-14. The volume is rounded off with a response by Mason to these scholars an.